Hidden corrosion recognition by thermography - Andonova, Anna (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Detecting and evaluating hidden corrosion remains a challenging task in many vital industrial areas. Infrared thermography (IRT) is a remote and fast diagnostic tool. Thanks to the rapid development of electronic devices and the new construction of equipment, thermography has become more popular. There are new applications for this technology for corrosion recognition in engineering and the army.An approach of IRT technique is discussed that eliminates the need for prior knowledge of a corrosion free area to allow automatic identification of corrosion areas from thermograms. This technique can be utilized in both static and active nondestructive (NDE) IRT modes.The paper presents the comparison of the results obtained by experimental measurements.